2014
DOI: 10.4041/kjod.2014.44.3.113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various toothpastes on remineralization of white spot lesions

Abstract: ObjectiveThe purpose of this in vitro study was to examine the effects of fluoridated, casein phosphopeptide.amorphous calcium phosphate complex (CPP-ACP)-containing, and functionalized β-tricalcium phosphate (fTCP)-containing toothpastes on remineralization of white spot lesions (WSLs) by using Quantitative light-induced fluorescence (QLF-D) Biluminator™ 2.MethodsForty-eight premolars, extracted for orthodontic reasons from 12 patients, with artificially induced WSLs were randomly and equally assigned to four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Commonly used fluoridated toothpastes are NaF, SnF2, monofluorophosphate or a combination of these. Newer remineralising agents such as CPP-ACP (casein phosphopeptide amorphous calcium phosphate) and Biomin F have also been recently introduced (4).…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used fluoridated toothpastes are NaF, SnF2, monofluorophosphate or a combination of these. Newer remineralising agents such as CPP-ACP (casein phosphopeptide amorphous calcium phosphate) and Biomin F have also been recently introduced (4).…”
Section: Introductionmentioning
confidence: 99%
“…They noticed a significant difference between these groups, as the one with the fluoride toothpaste presented a reduced clinical index [16]. Various other toothpastes were tested on demineralized teeth such as the study from Jo et al [17], who compared fluoride toothpaste, casein phosphopeptide amorphous calcium phosphate complex (CPP-ACP) and functionalized β-tricalcium phosphate (fTCP) containing toothpaste [17]. They seem to have found that sodium fluoride toothpaste and CPP-ACP are more effective in reducing white spot lesions [17].…”
Section: Resultsmentioning
confidence: 99%
“…Various other toothpastes were tested on demineralized teeth such as the study from Jo et al [17], who compared fluoride toothpaste, casein phosphopeptide amorphous calcium phosphate complex (CPP-ACP) and functionalized β-tricalcium phosphate (fTCP) containing toothpaste [17]. They seem to have found that sodium fluoride toothpaste and CPP-ACP are more effective in reducing white spot lesions [17]. On the contrary, Ballard et al [18] who studied three commercial toothpastes NovaMin (Dr. Collins Inc), Prevident5000 (Colgate, New York, NY) and MIPastePlus (GC America, Alsip, Ill) found no significant difference between them regarding the lesions [18].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the ∆Q values in the current study were expressed as negative values accompanying the unit of "%pixels." As the QLF-D facilitates a noninvasive method of evaluating enamel density, it is applied in both in vivo and in vitro studies all over the world [7] [19].…”
Section: Discussionmentioning
confidence: 99%